A Note on Hamiltonian Bypasses in Digraphs with Large Degrees - Darbinyan, Samvel Kh. (Mathematical Problems of Computer Science, 2021)
Let D be a 2-strongly connected directed graph of order p ≥ 3. Suppose that d(x) ≥ p for every vertex x ∈ V (D) \ {x0}, where x0 is a vertex of D. In this paper, we show that if D is Hamiltonian or d(x0) > 2(p − 1)/5, then D contains a Hamiltonian path, in which the initial vertex dominates the terminal vertex.